The Impact of Improved Flying Swallow Combined Pillow Waist Method on Lumbar Disc Herniation - Zhou, Yongdong; Gui, Shaohong; Shi, Yan; Xu, Jing; Li, Shanzhi; Liu, Wenping (Journal of Contemporary Medical Practice, 2025)
Objective To explore the clinical efficacy and quality of life impact of the improved Flying Swallow training combined with pillow waist therapy for patients with lumbar disc herniation (LDH). Methods A total of 86 LDH patients were randomly and evenly divided into a control group and an observation group. The control group received improved Flying Swallow functional exercises and oral Celecoxib capsules, while the observation group additionally received waist pillow therapy. After one week of continuous treatment, changes in VAS scores, SCODI index, WHOQOL scores, lumbar physiological curvature, straight leg raise height, and clinical efficacy assessment were compared between the two groups. Results The cure and effectiveness rate in the observation group was significantly higher than that in the control group (P<0.01). VAS scores, SCODI index, lumbar physiological curvature, and WHOQOL scores were all significantly better in the observation group compared to the control group (P<0.05), but the difference in straight leg raise height was not significant (P>0.05). Conclusion The improved Flying Swallow training combined with pillow waist therapy can effectively alleviate clinical symptoms of LDH and improve quality of life, warranting further exploration and promotion in clinical practice.